The Point Men - John, Glen.; Cal, Macaninch; Donald Sumpter; Kerry Fox; Maryam d'Abo; Nicolas de Pruyssenaere; Vincent Regan; Christopher Lambert (UK France Luxembourg Carousel Picture Company, 2001)
After botching a mission to kill Palestinian terrorist Amar (Vincent Regan), Israeli secret service agent Tony Eckhardt (Christopher Lamber) and his team are demoted and become an embarrassment to their agency. Eckhardt becomes convinced that the operation failed due to a trap set by Amar. When his fellow team members begin dying one-by-one under suspicious circumstances, Eckhardt must make his own plans to handle the situation.
Steven Hartov
Languages : English, Turkish
Subtitles : English, Turkish
Keywords: Drama; Action